2002
DOI: 10.1071/ar01140
|View full text |Cite
|
Sign up to set email alerts
|

Shearing ewes at mid-pregnancy is associated with changes in fetal growth and development

Abstract: This study investigated the effect of mid-pregnancy shearing (at Day 70 of pregnancy, P70) on herbage intake of grazing single- and twin-bearing ewes, lamb birth weight, and cold resistance of new-born lambs. At pregnancy diagnosis on P50, 30 single-bearing and 30 twin-bearing ewes were allocated either to be shorn at P70 (n = 15 for each pregnancy rank) or to remain unshorn to serve as controls (n = 15 for each pregnancy rank). All ewes were mated over a 3-day period with synchronisation of their oestrus. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 30 publications
3
23
0
1
Order By: Relevance
“…In previous studies that have reported the effect of birthsize on the proportionality of organs in singles and twins, it has been observed that the smaller fetuses tend to display heavier not lighter organ weights especially the heart and liver (Clarke et al, 1997;Revell et al, 2002;Harding, 2001). Therefore in the present study, it might have been expected that the triplets, which were lighter on average than their twin born counterparts, would have displayed greater organ weights after correction for body weight.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In previous studies that have reported the effect of birthsize on the proportionality of organs in singles and twins, it has been observed that the smaller fetuses tend to display heavier not lighter organ weights especially the heart and liver (Clarke et al, 1997;Revell et al, 2002;Harding, 2001). Therefore in the present study, it might have been expected that the triplets, which were lighter on average than their twin born counterparts, would have displayed greater organ weights after correction for body weight.…”
Section: Discussionmentioning
confidence: 57%
“…Robinson (1977) stated that there was no evidence to suggest there is differential growth in fetal organs or tissues in comparison to fetal weight under conditions of under nutrition. More recently Clarke et al (1997), Harding (2001) and Revell et al (2002) reported that at least in singles and twins, treatments which resulted in smaller lambs also resulted in changes in the relative sizes of many organs. It appears that a detailed comparison of twin-and triplet-fetuses in late pregnancy has not been undertaken.…”
Section: Introductionmentioning
confidence: 96%
“…However, increases in birth weight resulting from midpregnancy shearing have been observed without a corresponding increase in gestation length (Kenyon et al, 2002c;Corner et al, 2006). In studies where there was an increase in gestation length the duration was insufficient to account for the entire difference in lamb birth weight (Kenyon et al, 2002b;Revell et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…An increase in the birth weight of light-weight lambs has the potential to increase survival rates to weaning (Morris et al, 1999). Mid-pregnancy shearing has consistently increased lamb birth weights (Morris and McCutcheon, 1997;Morris et al, 2000;Smeaton et al, 2000;Kenyon et al, 2002a,b,c;Revell et al, 2002;Kenyon et al, 2004;Corner et al, 2006). However, in New Zealand, mid-pregnancy shearing takes place in the winter when conditions can be cold, wet and windy and may result in hypothermia (Morris et al, 1962) with ewe mortality rates of 3-14% (Dabiri et al, 1995).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation